2015
DOI: 10.1246/cl.150385
|View full text |Cite
|
Sign up to set email alerts
|

Determination of Chloride Content in Planar CH3NH3PbI3−xClx Solar Cells by Chemical Analysis

Abstract: Methylammonium lead mixed-halide perovskite (CH 3 NH 3 -PbI 3¹x Cl x ) has been widely used for photovoltaic conversion. Supposedly, the presence of chloride ions in perovskite precursors enhances the coverage, morphology, and stability of the final perovskite film. It also improves carrier diffusion length in the perovskite film. Due to these advantages, the mixed-halide compound has been adopted for use in planar structure perovskite solar cells and it has led to significant enhancement in power conversion e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
26
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 34 publications
(32 citation statements)
references
References 25 publications
2
26
0
Order By: Relevance
“…The effects of halogen doping and HTL on photovoltaic properties and microstructure on organic-inorganic hybrid heterojunction solar cells using the perovskite compound have been studied for improving photovoltaic performance and optical properties. In particular, the influence of halogen doping on iodide, bromine and chlorine halide perovskite structures in the hybrid solar cells have been characterized for optimizing band gap, crystal structure, optical and photovoltaic properties and conversion efficiency [11][12][13]. The role of halogen doping using iodine (I), bromine (Br) and chlorine (Cl) compounds as the dopant and the HTL on the photovoltaic and structural properties is an important factor to optimize the improvement of carrier-generation, carrier diffusion, transporting properties and photovoltaic performance.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The effects of halogen doping and HTL on photovoltaic properties and microstructure on organic-inorganic hybrid heterojunction solar cells using the perovskite compound have been studied for improving photovoltaic performance and optical properties. In particular, the influence of halogen doping on iodide, bromine and chlorine halide perovskite structures in the hybrid solar cells have been characterized for optimizing band gap, crystal structure, optical and photovoltaic properties and conversion efficiency [11][12][13]. The role of halogen doping using iodine (I), bromine (Br) and chlorine (Cl) compounds as the dopant and the HTL on the photovoltaic and structural properties is an important factor to optimize the improvement of carrier-generation, carrier diffusion, transporting properties and photovoltaic performance.…”
Section: Introductionmentioning
confidence: 99%
“…The role of halogen doping using iodine (I), bromine (Br) and chlorine (Cl) compounds as the dopant and the HTL on the photovoltaic and structural properties is an important factor to optimize the improvement of carrier-generation, carrier diffusion, transporting properties and photovoltaic performance. Quantitative investigation into the photovoltaic and optical properties of the perovskite structure with molar ratio dependence of I, Cl and Br compounds has been performed [13]. Control of halogen doping with molar ratio between I, Cl and Br in perovskite crystal structure will provide the best condition for the photovoltaic performance, the crystal structure, carrier mobility and electronic electronic structure with band gaps between the highest occupied molecular orbital (HOMO) and lowest unoccupied molecular orbital (LUMO) and the optical properties with a wide range of absorption.…”
Section: Introductionmentioning
confidence: 99%
“…After annealing the perovskite layer, the final compound formed is essentially CH 3 NH 3 PbI 3 , although a trace amount of chloride can be found in the device. 16 Finally, the hole transport layer was deposited on the perovskite layer.The XRD pattern of CH 3 NH 3 PbI 3 without bias voltage in the dark was measured under standard conditions at room temperature ( Figure S1). The characteristic peaks at 14.1, 28.5, and 43.3°are attributed to the (110), (220), and (330) planes confirm the tetragonal I4/mcm space group at room temperature.…”
mentioning
confidence: 99%
“…It has been proved by different chemical analysis methods such as titration or ion chromatography that a trace amount of chloride can be still found in the device. 6,8 The chemical formula CH 3 NH 3 PbI 2.94 Cl 0.06 with a chloride content of less than 2% from the total halide ions has been proposed. 6 Pool et al 9 also found x = 0.05 for their annealed perovskite films.…”
mentioning
confidence: 99%
“…6,8 The chemical formula CH 3 NH 3 PbI 2.94 Cl 0.06 with a chloride content of less than 2% from the total halide ions has been proposed. 6 Pool et al 9 also found x = 0.05 for their annealed perovskite films. In the case of Li et al, 8 x = 0.17 was estimated by potentiometric titration.…”
mentioning
confidence: 99%